Post Disaster Relocation Issues: A Case Study of Samasarakanda Landslide in Sri Lanka - Sangasumana, Pinnawala (European Scientific Journal, ESJ, 2018)
Landslide-induced displacement is an unexpected tragedy as well as a major development constraint which cannot be overcome sustainably unless a well-established mechanism is functionalized. Since the displacement is a life changing event, the attention should be focused to address all aspects of restoration of lives such as building houses, establishing livelihood opportunities, rehabilitation and reintegration in the process of relocation. In order to address the relocation issues and challenges for seeking durable solutions, community based strategies are most welcome in contemporary disaster management plans. In addition to examine the failures of existing relocation programmes, this study has attempted to investigate one of the neglected aspects of restoring displaced lives in the recovery phase of disaster management cycle; post-relocation satisfaction. The methodology has initially been designed based on qualitative approach focusing 72 households selected through judgment sampling from six relocated housing schemes after the massive landslide occurred in 2016 at Aranayaka division in Kegalle District, Sri Lanka. Both quantitative and qualitative techniques have been used for data collection through questionnaires, structural interviews, semi structural interviews and case studies while descriptive data analytical methods applied particularly for case study interpretation. The research results revealed that, this unexpected landslide hazard has created several socio-economic constraints which cause to accelerate the relocation issues. Lack of involvement of the government institutions in finding durable solutions at the recovery phase and the delay of policy implementation are identified as the main interlinked issues in the process of relocation. Due to the lack of community participation in project planning and less cooperation between the authorities and the public, most of the relocation programmes could not achieve the expected project deliverables. Therefore the research paper suggests new strategies to overcome the existing issues and challenges in order to minimize the problems faced by post-landslide relocated communities.